Validation of the transactional eHealth literacy instrument with cancer caregivers - Taylor S. Vasquez; Carma L. Bylund; Carla L. Fisher; Samantha R. Paige (Elsevier, 2022)
Objective: Family members are important sources of support for patients with cancer. They access, evaluate, and engage with online information and discuss it with a cancer clinician. This study validates the 4-dimensions, 18-item Transactional eHealth Literacy Instrument (TeHLI) and proposed to include Clinical eHealth Literacy as a 5th dimension. Methods: The Leukemia & Lymphoma Society (LLS) disseminated an online survey to 121 family member caregivers between March-June 2020. We conducted confirmatory factor analyses (1) to examine model fit for the 4-factor TeHLI in the cancer caregiver population, and (2) to examine the model fit when adding the 5th factor. Results: The 4-dimension model yielded acceptable model fit (RMSEA = 0.09; 90% CI = 0.08-0.11; CFI = 0.98; TLI = 0.98; SRMR = 0.07). The 5-dimension model also yielded acceptable model fit (RMSEA = 0.08; 90% CI = 0.07-0.10; CFI = 0.97; TLI = 0.97; SRMR = 0.08), supporting the expansion of the TeHLI within this population. Conclusion: The five-dimension TeHLI is a valid and reliable measure of eHealth literacy among blood cancer caregiver populations. Innovation: The TeHLI can be used as an outcome measure for communication skills training for caregivers, patients, and clinicians.